STRATEGIES FOR MANAGING OIL SPILL RELATED CONFLICTS IN THE NIGER DELTA: A CASE STUDY OF BAYELSA STATE - Chijioke, Ndidiamaka; Audu-Bako, Susan; Uwakwe, Ikechukwu (Advances in Social Sciences Research Journal, 2021)
The discovery of crude oil in Oloibiri-a town in the present Bayelsa state, Niger-Delta region of Nigeria) in 1956 and the subsequent exploration activities have over the years impacted tremendously not only on the ecosystem and livelihood pattern of the Niger Delta but on the pattern of conflicts that has trended.. While resources accruable to Nigeria from sale of crude oil are shared by all, the impacts of oil spill an offshoot of crude oil exploration activities are borne solely by the Niger Delta region. Oil spill appears to have found a permanent abode in Bayelsa state; from Southern Ijaw to Sagbama local governments, Olodiama to Azuzuama communities. Local communities are faced with the problem of continuous oil spill. This in turn has brought about conflicts between oil bearing communities and oil companies. These conflicts in some instances led to shut down of operations of oil companies, vandalism, and reduction of Nigeria’s crude export. In view of the illustrated background, this study examined the strategies for management of oil spill related conflicts in Bayelsa state regarding that oil spill is a key impact of crude oil exploration activity. Findings revealed that the strategies deployed in the management of oil spill in the state can be categorised into three: community strategies, regulators and non-governmental organisations strategies.